Analisis ketahanan pangan fungsional berbasis kearifan lokal “uma lengge” dalam mendukung pencapaian SDGs - Nur Fitrianingsih; Darmin Darmin; Hairunnisah Hairunnisah; Dea Zara Avila (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Food security is a strategic issue in sustainable development, directly related to meeting the basic needs of the community. The community of Maria Village, Bima Regency, possesses local wisdom in the form of Uma Lengge, which functions as a traditional food barn for long-term storage of agricultural produce. This system not only maintains food availability but also maintains cultural values ​​and social solidarity. Purpose: To analyze functional food security based on the local wisdom of Uma Lengge in supporting the achievement of sustainable development goals (SDGs). Method: Using a qualitative approach with sociocultural phenomenology, the study was conducted in Maria Village, Wawo District, Bima Regency through participatory observation, in-depth interviews, and documentation with traditional leaders, Uma Lengge users, and the village government. Results: The study shows that Uma Lengge functions as a traditional food storage system that maintains food availability, strengthens social solidarity, maintains local cultural values, and supports the achievement of the SDGs, particularly the goals of zero poverty, zero hunger, and a healthy and prosperous life. Conclusion: Uma Lengge is a form of food security based on local wisdom that remains relevant in supporting sustainable development and can be used as a model for strengthening local food systems. Suggestion: Future research should quantitatively measure the impact of Uma Lengge on household food security status and community nutrition indicators. Furthermore, further studies are needed to integrate traditional food systems with SDG-based regional development programs. Keywords: Food Security; Local Wisdom; Sustainable Development Goals (SDGs); Uma Lengge.